The Influence of Internal And External Factors On The Entrepreneurial Interest of Fashion Design Students At Pencawan Vocational School, Medan - Angel Angel; Tri Utari Ismayuni (International Journal of Science and Environment (IJSE), 2025)
This study aims to analyze the influence of internal and external factors on the entrepreneurial interest of Fashion Design students at Pencawan Vocational High School, Medan. The study used a quantitative approach with multiple linear regression. The research sample was 32 grade XI students selected through total sampling. The research instrument was a questionnaire whose validity and reliability had been tested. The results showed that internal factors contributed positively but not significantly to entrepreneurial interest (t = 1.121; Sig. = 0.272), while external factors had a significant influence (t = 2.751; Sig. = 0.010). Simultaneous tests showed that both factors together had a significant influence on entrepreneurial interest (F = 7.862; Sig. = 0.002), with external factors being more dominant (β = 0.704) than internal factors (β = 0.270). Thus, family, school, and environmental support play a greater role in increasing students' entrepreneurial interest, while internal factors function as supporting capital.